Effects of Coleus Forskohlii Supplementation on Body Composition and Hematological Profiles in Mildly Overweight Women - Kreider Richard B; Thomas Ashli; Ounpraseuth Song; Bowden Rodney; Magrans Terri; Milnor Pervis; Almada Anthony; Earnest Conrad; Greenwood Mike; Cowan Patty; Melton Charlie; Smith Penny; et al. (Taylor & Francis Group, 2005)
Abstract Purpose This study investigated the effects of Coleus Forskohlii (CF) on body composition, and determined the safety and efficacy of supplementation. Methods In a double blind and randomized manner, 23 females supplemented their diet with ForsLean™ (250 mg of 10% CF extract, (n = 7) or a placebo [P] (n = 12) two times per day for 12-wks. Body composition (DEXA), body weight, and psychometric instruments were obtained at 0, 4, 8 & 12 weeks of supplementation. Fasting blood samples and dietary records (4-d) were obtained at 0 and 12-wks. Side effects were recorded on a weekly basis. Data were analyzed by repeated measures ANOVA and are presented as mean changes from baseline for the CF and placebo groups, respectively. Results No significant differences were observed in caloric or macronutrient intake. CF tended to mitigate gains in body mass (-0.7 ± 1.8, 1.0 ± 2.5 kg, p = 0.10) and scanned mass (-0.2 ± 1.3, 1.7 ± 2.9 kg, p = 0.08) with no significant differences in fat mass (-0.2 ± 0.7, 1.1 ± 2.3 kg, p = 0.16), fat free mass (-0.1 ± 1.3, 0.6 ± 1.2 kg, p = 0.21), or body fat (-0.2 ± 1.0, 0.4 ± 1.4%, p = 0.40). Subjects in the CF group tended to report less fatigue (p = 0.07), hunger (p = 0.02), and fullness (p = 0.04). No clinically significant interactions were seen in metabolic markers, blood lipids, muscle and liver enzymes, electrolytes, red cells, white cells, hormones (insulin, TSH, T3, and T4), heart rate, blood pressure, or weekly reports of side effects. Conclusion Results suggest that CF does not appear to promote weight loss but may help mitigate weight gain in overweight females with apparently no clinically significant side effects.